Pengaruh Kompetensi Dosen Terhadap Motivasi Belajar Pada Mahasiswa Prodi Manajemen Universitas Nusa Putra - Heliani; Mia Safitri Rahayu; Siswanto, Junaedi; Faris, Riyan Mirdan (Universitas Nusa Putra, 2020)
The number of phenomena of low learning motivation among students, this study aims to see the effect of lecturer competence on learning motivation in students of the Management Study Program at the University of Nusa Putra. This research also aims to broaden the knowledge of researchers and train scientific thinking. In this study, the population used was 101 people. While the research sample used purposive sampling. Based on certain criteria, a sample of 85 people was obtained. Data analysis used normality test, product moment correlation analysis, and simple linear regression analysis. This study succeeded in revealing that the competence of lecturers on the learning motivation of management students at the University of Nusa Putra had an effect but not significantly as much as 11,3%.